Marginal probability distributions of random sets in R with Markovian refinements - Virchenko, Yu.P.; Shpilinskaya, O.L. (Інститут математики НАН України, 2005)
Marginal probability distributions describing statistically random sets in R losed with probability one are introduced. These distributions are calculated in the case of random sets with Markovian reﬁnements.